Comparative Efficacy of TOF MRA and CT Angiography in Cerebrovascular Disease Diagnostics - Farzaneh, Khoroushi; Toosi, Farrokh Seilanian; Amirhossein, Fathabadi; Behzad, Aminzadeh; Lida, Jarrahi; Narges, Sheibak (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
To compare the diagnostic value of 3D Time-of-Flight Magnetic Resonance Angiography (3D TOF MRA) with Computed Tomography Angiography (CTA) in assessing cerebrovascular disease (CVD).A retrospective observational study included 205 adult patients who underwent both TOF MRA and CTA scans. Demographic data, clinical symptoms, and imaging findings were analyzed. Diagnostic parameters were calculated for TOF MRA using CTA as the reference standard.Among 205 patients (mean age: 60 ± 11.67 years), TOF MRA detected more vessel occlusions (45.9%) than CTA (39%). CTA, however, identified more aneurysms (2.9% versus 1.5%). TOF MRA showed a sensitivity of 88%, specificity of 76%, and overall diagnostic efficacy of 84%. A significant association between CVD changes detected by MRA and CTA was observed (p < 0.001).TOF MRA demonstrated a higher detection rate for vessel occlusions but was less effective than CTA in detecting vessel stenosis and aneurysms. TOF MRA is safer for repeated use and in patients with renal insufficiency due to the absence of contrast agents and ionizing radiation. However, its lower spatial resolution may lead to misclassification.
Keywords: cerebrovascular disease; image quality; CTA; time-of-flight MRA